Chess not checkers : elevate your leadership game - Miller, Mark, 1959- (BK business book., 2015)
As organizations grow, the demands on leadership change. The same old moves won't cut it any more. In Chess Not Checkers, Miller tells the story of Blake Brown, newly appointed CEO of a company troubled by poor performance and low morale. Nothing Blake learned from his previous job seems to help him deal with the issues he now faces. The problem, his new mentor points out, is Blake is playing checkers ; he needs to play chess or he's going to lose. The early days of an organization are like checkers: a quick game with mostly interchangeable pieces. Everybody does a little bit of everything, the leader included, and things are so frantic you just have to react as fast as you can. But as the organization expands, you can't just keep jumping from activity to activity. You have to think strategically, look ahead, leverage every employee's specific talents. That's chess. And this approach creates unprecedented levels of performance. Adapting four strategies from the game of chess, Miller reveals four moves high-performance organizations make. They bet on leadership, act as one, win the heart, and excel at execution. Chess Not Checkers is an accessible and easily applied guide to help leaders elevate their own leadership and the performance of their entire team.